Hambatan Penyelenggaraan Pendidikan di Fakultas Ilmu Pendidikan - S. Mundzir; Sulthon Sulthon (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This study attempts to find out the problems faced by the faculty of Education State University of Malang in carrying out academic activities. Employing a mixed-methodology design, this study involved students, lecturers, and administrative staff. The data were collected through questionnaires focusing on the planning, implementing, and assessing processes. The findings suggest that there were problems in lecture scheduling, lecture implementation, evaluation system and grade recording.